Айсберг под сердцем: [роман] / Наталья Андреева - Андреева Наталья Вячеславовна (Детектив-загадка, 2016)
Экземпляры: аб. (20180524) / Инвентарный номер: 58447 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44